Anak Perempuan sebagai Agen Perubahan: Analisis Multidimensi dari Perspektif Agama, Feminisme, dan Realitas Sosial (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2025)
This study examines the role of girls in the family from the perspective of Islam, feminist theory, and modern empirical research, as well as the factors that influence changes in gender dynamics in modern families. Using a literature review method, this study analyzes religious texts such as Surah An-Nisa verses 11-12, Simone de Beauvoir's feminist theory, and the results of empirical research related to women's contributions to the family. The results show that the role of girls is multidimensional, covering domestic, economic, and social aspects. From an Islamic perspective, the principle of justice in the distribution of inheritance and the hadith of the Prophet Muhammad SAW emphasize the importance of women's rights. Feminist theory offers a critique of patriarchal structures that underestimate the potential of girls, while empirical research shows their real contribution to family resilience. Factors such as reinterpretation of religious values, globalization, education, economic roles, and media representation are the main drivers of changes in gender dynamics. This study concludes that girls have great potential as agents of change, but the main challenge lies in integrating modern values ​​with local contexts to realize gender equality.